Expression and function of the insulin receptor in normal and osteoarthritic human chondrocytes: modulation of anabolic gene expression, glucose transport and GLUT-1 content by insulin - Rosa, SC (2011)
OBJECTIVE: Chondrocytes respond to insulin, but the presence and role of the specific high affinity insulin receptor (InsR) has never been demonstrated. This study determined whether human chondrocytes express the InsR and compared its abundance and function in normal and osteoarthritis (OA) human chondrocytes. DESIGN: Cartilage sections were immunostained for detection of the InsR. Non-proliferating chondrocyte cultures from normal and OA human cartilage were treated with 1nM or 10nM insulin for various periods. InsR, insulin-like growth factor receptor (IGFR), aggrecan and collagen II mRNA levels were assessed by real time RT-PCR. InsR, glucose transporter (GLUT)-1, phospho-InsRbeta and phospho-Akt were evaluated by western blot and immunofluorescence. Glucose transport was measured as the uptake of [3H]-2-Deoxy-d-Glucose (2-DG). RESULTS: Chondrocytes staining positively for the InsR were scattered throughout the articular cartilage. The mRNA and protein levels of the InsR in OA chondrocytes were approximately 33% and 45%, respectively, of those found in normal chondrocytes. Insulin induced the phosphorylation of the InsRbeta subunit. Akt phosphorylation and 2-DG uptake increased more intensely in normal than OA chondrocytes. Collagen II mRNA expression increased similarly in normal and OA chondrocytes while aggrecan expression remained unchanged. The Phosphoinositol-3 Kinase (PI3K)/Akt pathway was required for both basal and insulin-induced collagen II expression. CONCLUSIONS: Human chondrocytes express functional InsR that respond to physiologic insulin concentrations. The InsR seems to be more abundant in normal than in OA chondrocytes, but these still respond to physiologic insulin concentrations, although some responses are impaired while others appear fully activated. Understanding the mechanisms that regulate the expression and function of the InsR in normal and OA chondrocytes can disclose new targets for the development of innovative therapies for OA.